ANALISIS PENGARUH FAKTOR SOSIAL EKONOMI RUMAH TANGGA TERHADAP FERTILITAS DI SUMATERA BARAT - Defiana Larasati; Idris Idris; Ali Anis (Universitas Negeri Padang, 2018)
This study aims to determine and analyze (1) The influence of the job of the head of household to fertility in West Sumatra. (2) The effect of expenditure per capita household on fertility in West Sumatra. (3) The contraceptions effect on fertility in West Sumatera. (4) Influence of mother education level to fertility in West Sumatera. (5) Influence of education level of father to fertility in West Sumatra. (6) Influence of residence area to fertility in West Sumatra.The type of research is descriptive and associative research. The type of data in this study is the Susenas data of district / city in West Sumatra Province in 2016. The study populations are the mothers who gave birth to living childs in West Sumatra. The total sample is 5014 people. Samples were taken from 19 regencies / cities in West Sumatera province in both urban and rural areas. Hypothesis test is G test and Wald test with 5% real level. The results of this study show that (1) the head of household job has a positive and significant effect on fertility in West Sumatra. (2) The expenditure per capita household has a positive and significant effect on fertility in West Sumatra. (3) The contraception is used by mothers has a negative and significant effect on fertility in West Sumatra. (4) the education level of mothers have a positive and significant effect on fertility in West Sumatra. (5) The education level of the father has a positive and significant effect on fertility in West Sumatra. (6) Residential areas have a negative and insignificant effect on fertility in West Sumatra. (6) The work of household head, expenditure per capita household, family planning, mother education, father education and residence have a positive and significant influence on fertility in West Sumatra. Keywords: fertility, occupation of head of household, expenditure per capita household, use of family planning, mother education, father education and residence.